(3MeGjI GdeSJgdc aj Gdabg GdGbJUGOj GdGSdGej(B-(3OQGSI ebGQfI(B-s - (3YHOg(B, (3ehab eMeOs ((3YeGfs (3GdeLOdGhjs, 2002)
(3GdGSJgdGc,GdGfJGL,GdhSGFd GdJj GJHYgG GdGSdGe dMeGjI GdeSJgdcs
Keywords: (3GdeSJgdchfs; (3MeGjI GdeSJgdcs